Realia as a Media to Improve the EFL Learners’ Achievements in Descriptive Writing - Sumarsih, Sumarsih (Association of Language Teachers in Southeast Asia (ALTSA), 2019)
This study was aimed at investigating the improvement of EFL learners? achievement in writing descriptive paragraph in Indonesia. Therefore, the moethodology conducted in this study was action research. The techniques of collecting data were documentation (writing test) and questionnaire for quantitative data, and observation and interview for the qualitative data. The result shows that the score mean of EFL learners was improved from cycle 1 to cycle 2 which was 66.28 to 87.00 respectively. Furthermore, the result of questionnaire shows that most of EFL learners were very interested and enjoying learning writing by using realia. Moreover, from the observation and interview, EFL learners said that realia is very good and enjoyable to improve their achievements in descriptive writing. Therefore, relia should be implemented to teach English in Indonesia not only to teaching writing but also to teach other skills such as listening, speaking and reading